MORPHOLOGICAL AND FUNCTIONAL CHARACTERISTICS OF THE HANDBALL PLAYERS AT THE PUBERTY AGE - Capaţina Gregory; Verejan Ruslan (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The identification of morphological and functional characteristics of adolescents allows programming the suitable effort of sports training in handball game. Programming of sports training for handball players at pubertal age requires individual biological characteristics, leading to changes in several systems of the body such as: musculoskeletal, respiratory, cardiovascular, as well as of in the central and peripheral nervous system.